2016
DOI: 10.1007/s10461-016-1413-y
|View full text |Cite
|
Sign up to set email alerts
|

Social Network Strategies to Address HIV Prevention and Treatment Continuum of Care Among At-risk and HIV-infected Substance Users: A Systematic Scoping Review

Abstract: Social network analysis (SNA) and social network-based interventions (SNI) are important analytical tools harnessing peer and family influences critical for HIV prevention and treatment among substance users. While SNA is an effective way to measure social network influences, SNI directly or indirectly involves network members in interventions. Even though these methods have been applied in heterogeneous ways, leading to extensive evidence-based practices, systematic reviews are however, lacking. We searched f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
70
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 96 publications
(189 reference statements)
0
70
0
2
Order By: Relevance
“…], HIV prevention or treatment [Ghosh et al. ], project management [Zheng et al. ]) are not immune from similar shortcomings to the SNA research we reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…], HIV prevention or treatment [Ghosh et al. ], project management [Zheng et al. ]) are not immune from similar shortcomings to the SNA research we reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…Another study with injecting drug users in Lithuania found that betweenness centrality was associated with HIV prevalence, highlighting the importance of engaging people with high betweenness centrality as peer educators in HIV prevention interventions (50). Strategically recruiting individuals who occupy certain positions in their networks in line with a recent review of social network strategies to prevent HIV that recommended that future network interventions “optimally use the power of social networks to reduce HIV transmission” (10). To fully understand the role of network position in influencing health leader’s performance in HIV prevention trials, however, research that longitudinally examines the co-evolution of social networks and intervention-related communication patterns is needed.…”
Section: Discussionmentioning
confidence: 99%
“…network size, structure, composition, and norms) with HIV testing (1, 2), injecting drug use (3, 4), intimate partner violence (5, 6), as well as risky sexual behaviors (79). Engaging social networks in HIV prevention interventions, therefore, provides an opportunity to target these network-level factors by leveraging the peer influence processes underpinning associations between network-level determinants and the HIV-related behaviors of network members (10). …”
Section: Introductionmentioning
confidence: 99%
“…7,27,28 Indeed, network-based or peer-interventions targeting a reduction in risk behaviors, such as syringe sharing have been shown to be feasible and efficacious. For example, peer-intervention studies conducted in Baltimore found lower engagement in HIV risk behavior among active PWID who were trained to be peer educators within their networks compared to those who did not receive training.…”
Section: Discussionmentioning
confidence: 99%
“…However, as noted in a recent systematic review, little is known about how network characteristics are associated with outcomes along the HIV care continuum. 7 As a consequence, while several network based interventions have focused on HIV prevention via reducing risk behaviors 8,9 , these types of interventions should also consider targeting adherence to antiretroviral therapy (ART) and achieving viral suppression.…”
Section: Introductionmentioning
confidence: 99%